SYSTEM SALES IN COOPERATION sembako PT. Pondok Indah GOLF USING MICROSOFT VISUAL BASIC 6.0 - Nurkholifah Nurkholifah; Ire Puspa Wardhani, Skom, MMSI (Jurnal Sistem Informasi, 2006)
The need for systems that support to get the information fast, accurate, relevant andtimely. And of the PT. Pondok Indah require computerized system as a supporter,who not only produce the information fast, accurate, relevant and timely, but as a safestorage place to assist decision makers.